India's energy revolution : insights into the becoming of a global power - Styczynski, Annika Bose (Routledge, Taylor & Francis Group, 2024)
"India is the third largest emitter of Greenhouse Gases which makes it an important player whose climate mitigation actions and inactions are closely scrutinised. This book studies developments in India's energy system from a governance perspective. It presents a unique compilation and synthesis of research findings that captures achievements, shortcomings, and persistent and transient challenges of India's transition towards a net-zero economy by 2070. The book grounds its analysis in domestically formulated goals and reflects on dynamics at the structural level of India's multi-scalar innovation system by highlighting the influencing factors of energy system status and change. It presents the perspectives and positions of different actor groups, studies the market and business, and discusses cases influenced by existing or changing institutions across the whole spectrum of energy resources from fossil to non-fossil fuels and respective technologies. The volume will be useful to students and researchers in energy governance, energy policy and economics, socio-technical transition studies, energy systems engineering, sustainable development, and environmental studies. It will also be of interest to policymakers and investors"-- Provided by publisher.
Keywords: Energy policy -- India.; Clean energy -- India.; Sustainable development -- India.; Business -- Environmental aspects -- India.; elektronické knihy; electronic books